Compressive and viscoelastic behavior of arenga pinnata-silicone biocomposite - Norhafizah Suhada, Abdullah (Elsevier Ltd, 2020)
This paper reports the compressive behavior of dry and soaked Silicone Biocomposite reinforced with Arenga Pinnata. In addition, for the first time load-unload tests were also carried out to highlight the hysteresis curves which reveal the viscoelastic behavior of Arenga Pinnata silicone biocomposite. Arenga Pinnata with several compositions of fiber (4 wt%, 8 wt%, 12 wt% and 16 wt%) was mixed with pure silicone and undergone compression set test (ASTM D395) and load unload tensile test (ASTM D412). For compression set test, the test was conducted in two conditions, which are dry and soaked specimens in seawater. The data from all the experiments had been analyzed to obtain compression set, stress strain relationship, and hysteresis loops. The results show that the compression set percentage peaked at 10% for silicone biocomposite of 16 wt%, and able to withstand 90 kPa compressive stress from the stress-strain curve. Hysteresis loop shows that the addition of Arenga Pinnata to pure silicone increases the energy dissipation of the material. This study discovered that the addition of different composition of Arenga Pinnata in pure silicone affects the mechanical behavior of the silicone biocomposite. More importantly, this study proves the viscoelasticity of this new material, Arenga Pinnata silicone biocomposite.